2010
DOI: 10.3109/01421590903548521
|View full text |Cite
|
Sign up to set email alerts
|

Using team-based learning to teach pharmacology to second year medical students improves student performance

Abstract: The results suggest that TBL provides a better outcome for students, and provide insight into appropriate design of TBL exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 19 publications
12
121
0
3
Order By: Relevance
“…Three hundred and thirty studies were identified, and 14 were included ( 2011; Willett et al 2011), two prospective cohort studies (Torralba et al 2009;Wiener et al 2009), one retrospective cohort study (Koles et al 2010), one concurrent cohort study (Zingone et al 2010) and seven non-concurrent cohorts (Nieder et al 2005;Levine et al 2004;Letassy et al 2008;Pileggi & O'Neill 2008;Mennenga 2010;Simaan et al 2010;Zgheib et al 2010). Of the 14 included studies, 12 took place in the United States, 1 in Lebanon (Zgheib et al 2010) and 1 in Austria (Wiener et al 2009). Thirteen of the studies concerned undergraduate education, including eight in medicine, three in pharmacy (Letassy et al 2008;Conway et al 2010;Zgheib et al 2010), one in dentistry (Pileggi & O'Neill 2008) and one in nursing (Mennenga 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three hundred and thirty studies were identified, and 14 were included ( 2011; Willett et al 2011), two prospective cohort studies (Torralba et al 2009;Wiener et al 2009), one retrospective cohort study (Koles et al 2010), one concurrent cohort study (Zingone et al 2010) and seven non-concurrent cohorts (Nieder et al 2005;Levine et al 2004;Letassy et al 2008;Pileggi & O'Neill 2008;Mennenga 2010;Simaan et al 2010;Zgheib et al 2010). Of the 14 included studies, 12 took place in the United States, 1 in Lebanon (Zgheib et al 2010) and 1 in Austria (Wiener et al 2009). Thirteen of the studies concerned undergraduate education, including eight in medicine, three in pharmacy (Letassy et al 2008;Conway et al 2010;Zgheib et al 2010), one in dentistry (Pileggi & O'Neill 2008) and one in nursing (Mennenga 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 included studies, 12 took place in the United States, 1 in Lebanon (Zgheib et al 2010) and 1 in Austria (Wiener et al 2009). Thirteen of the studies concerned undergraduate education, including eight in medicine, three in pharmacy (Letassy et al 2008;Conway et al 2010;Zgheib et al 2010), one in dentistry (Pileggi & O'Neill 2008) and one in nursing (Mennenga 2010). The only study that did not include undergraduate learners assessed internal medicine residents in their first, second and third postgraduate years (Torralba et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations